2019
DOI: 10.1002/ptr.6592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hibiscus sabdariffa (Roselle) supplementation in regulating blood lipids among patients with metabolic syndrome and related disorders: A systematic review and meta‐analysis

Abstract: This study aimed to assess the efficacy of Hibiscus sabdariffa (Roselle) in regulating blood lipids among patients with metabolic syndrome and related disorders. PubMed, the Cochrane Library, Embase, Web of Science, and Clinical Trials were searched to identify the randomised controlled trials meeting the inclusion criteria. Study selection, data extraction, and risk assessment were performed according to Cochrane handbook; available data were analysed using STATA 15.0 software. Eventually, nine trials involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…They have showed that sour tea can reduce cholesterol biosynthesis by inhibiting 3-hydroxy-3-methylglutarylcoenzyme A (HMG-CoA) reductase, which catalyzes the conversion of HMG-CoA to mevalonic acid, a necessary step in cholesterol biosynthesis, and can suppress TG synthesis (Duangjai et al, 2011;Yang et al, 2010). Sour tea flavonoids have a strong anti-oxidative activity on the liver, and they can affect the metabolism and production of lipids (Najafpour Boushehri et al, 2020;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They have showed that sour tea can reduce cholesterol biosynthesis by inhibiting 3-hydroxy-3-methylglutarylcoenzyme A (HMG-CoA) reductase, which catalyzes the conversion of HMG-CoA to mevalonic acid, a necessary step in cholesterol biosynthesis, and can suppress TG synthesis (Duangjai et al, 2011;Yang et al, 2010). Sour tea flavonoids have a strong anti-oxidative activity on the liver, and they can affect the metabolism and production of lipids (Najafpour Boushehri et al, 2020;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen of these studies were excluded because they included an abstract ( N = 5) or a protocol ( N = 1) only, were not published in English ( N = 1), had inappropriate exposures ( N = 2) or outcomes ( N = 1), or did not provide updated data ( N = 2). As a result, 50 systematic reviews and meta‐analyses were included in the final analysis (Figure 1; Amir Shaghaghi et al, 2013; Askari et al, 2019; Azhdari et al, 2019; Chen et al, 2020; Fatahi et al, 2019; Ghaedi et al, 2019; Ghaedi et al, 2020; Glisic et al, 2018; Gui et al, 2016; Hadi et al, 2018, 2020; Hadi, Pourmasoumi, Mohammadi, et al, 2019; Hadi, Pourmasoumi, Najafgholizadeh, et al, 2019; Hallajzadeh et al, 2020; Hamedifard et al, 2019; Han et al, 2019; Hasani et al, 2019; Hemati et al, 2020; Hernández‐García et al, 2019; Heshmat‐Ghahdarijani et al, 2020; Karimian et al, 2019; Khorshidi et al, 2020; Li et al, 2014, 2015, 2020; Maierean et al, 2017; Mansour‐Ghanaei et al, 2018; Mohammadi, Hadi, et al, 2019; Mohammadi, Ramezani‐Jolfaie, et al, 2019; Ostadmohammadi et al, 2019; Pourmasoumi et al, 2018, 2020; Rahmani et al, 2019; Rahmani et al, 2020; Ricci et al, 2010; Ried, 2016; Rocha et al, 2019; Sahebkar, 2014; Sahebkar, Simental‐Mendía, et al, 2016; Sahebkar, Soranna, et al, 2016; Salehi‐Sahlabadi et al, 2020; Serban et al, 2015; Shekarchizadeh‐Esfahani et al, 2020; Taku et al, 2010; Ursoniu et al, 2018; Zhang et al, 2020; Zhang, Yuan, et al, 2016; Zhang, Liu, et al, 2016; Zhu et al, 2017; Ziaei et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneous increment of health problems led into the attraction of global attention. Atherosclerosis, cardiovascular complications, pancreas disorders, and fatty liver are avowed as the concurrent disease with DLP (Zhang et al, 2020). Likewise, DLP is associated with metabolic syndrome (Mets) and its components such as obesity and diabetes (Tabatabaei-Malazy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse approaches are recommended to manage DLP; such as lifestyle modifications, diet intervention, and pharmacotherapy options (Shekarchizadeh-Esfahani et al, 2020). The more efforts do for the management of DLP, the less beneficial results the patients receive (Zhang et al, 2020). Despite the worldwide use of lipid-lowering agents, their long-term efficacy is still questionable (Shekarchizadeh-Esfahani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation